Bioinformatic Integration of Molecular Networks and Major Pathways Involved in Mice Cochlear and Vestibular Supporting Cells - Requena, Teresa; Gallego-Martinez, Alvaro; Lopez-Escamez, Jose A. (Frontiers in Molecular Neuroscience, 2018)
Background Cochlear and vestibular epithelial non-hair cells (ENHCs) are the supporting elements of the cellular architecture in the Organ of Corti and the vestibular neuroepithelium in the inner ear. Intercellular and cell-extracellular matrix interactions are essential to prevent an abnormal ion redistribution leading to hearing and vestibular loss. The aim of this study is to define the main pathways and molecular networks in the mouse ENHCs. Methods We retrieved microarray and RNA-seq datasets from mouse epithelial sensory and non-sensory cells from gEAR portal (http://umgear.org/index.html) and obtained gene expression fold-change between ENHCs and non-epithelial cells against hair cells for each gene. Differentially expressed genes (DEG) with a log2 fold change between 1 and -1 were discarded. The remaining genes were selected to search for interactions using Ingenuity Pathway Analysis and STRING platform. Specific molecular networks for ENHCs in the cochlea and the vestibular organs were generated and significant pathways were identified. Results Between 1,723 and 1,559 DEG were found in the mouse cochlear and vestibular tissues, respectively. Six main pathways showed enrichment in the supporting cells in both tissues: 1) “Inhibition of Matrix Metalloproteases”, 2) “Calcium Transport I”, 3) “Calcium Signaling”, 4) “Leukocyte Extravasation Signaling”, 5) “Signaling by Rho Family GTPases” and 6) “Axonal Guidance Signaling” (AGS). In the mouse cochlea, ENHCs showed a significant enrichment in 18 pathways highlighting “AGS” (p=4.37x10-8) and “RhoGDI Signaling” (p=3.31x10-8). In the vestibular dataset, there were 20 enriched pathways in ENHCs, the most significant being “Leukocyte Extravasation Signaling” (p=8.71x10-6), “Signaling by Rho Family GTPases” (p=1.20x10-5) and “Calcium Signaling” (p=1.20x10-5). Among the top ranked networks, the most biologically significant network contained the “auditory and vestibular system development and function” terms. We also found 108 genes showing tonotopic gene expression in the cochlear ENHCs. Conclusions We have predicted the main pathways and molecular networks for ENHCs in the Organ of Corti and vestibular neuroepithelium. These pathways will facilitate the design of molecular maps to select novel candidate genes for hearing or vestibular loss to conduct functional studies.